Wujudkan Jiwa Enterpreuner Mahasiswa Dan Meningkatkan UMKM Melalui Program Wirausaha Merdeka - Lenya Ramadhani; Ute Chairuz M.Nasution (Jurnal Manajemen Kreatif dan Inovasi, 2024)
It is hoped that the growth and development of entrepreneurship can reduce the number of unemployed and increase prosperity. The entrepreneurial spirit of today's students has begun to decline because most students who have the mindset of wanting to work for a company do not want to create jobs. Entrepreneurship is the ability and willingness to develop, manage and running a business, including taking the risks involved in it to achieve profits, therefore an entrepreneurial spirit is very important for students. There are very few MSMEs (Micro, Small and Medium Enterprises) nowadays due to people's interest in entrepreneurship and their lack of knowledge or insight into entrepreneurship.As for problems with MSMEs in Indonesia, such as weak business management capabilities, limited quality of human resources (HR), and weak access to financial institutions, especially banking. These businesses usually do not have a bookkeeping system, have difficulty expanding the business scale, and still have limited capital. Therefore, this independent entrepreneurship program can foster an entrepreneurial spirit and improve the quality of SMEs. The independent entrepreneurship program activities launched by the Ministry of Education and Culture are intended to study as well as exploring students' abilities to improve their entrepreneurial spirit and urging students to improve their entrepreneurial skills and make a positive impact on society.